Guided Inquiry Model with the REACT Strategy Learning Materials to Improve the Students’ Learning Achievement - Miftahul Jannah; Z. A. Imam Supardi; Prabowo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This study aims to describe the effectiveness of learning materials with a guided inquiry model with the REACT strategy to improve students’ learning achievement on heat and temperature topic. It developed with the 4D model and try outed using the One Group Pre-Test Post-Test Design. Data collection methods used validation, observation, and test. The results of this research are that the learning materials have a very valid category and it can be used to improve the learning process. The learning achievement, the average post-test score is 84 with an N-Gain of 0.7 which categorize as medium, while the overall student completeness reached 88.57%. The students have a very good response to learning in the range of the answer with agree and very agree. Based on the results of the study it can be concluded that learning materials of the guided inquiry learning model with the REACT strategy can improve the students’ learning achievement on heat and temperature topic. Guided inquiry with the REACT strategy learning is expected to be able to make students more actively in the process of gaining their knowledge directly so that students are easier to remember and interpret.